Design principles for social-ecological research at the landscape scale applied to western Rwanda - Matthias Baumann; Dula Duguma; Susanne Vögele; Meike Wollni; Ping Sun; Gaelle Ndayizeye; Joern Fischer (PLoS ONE, 2025)
Place-based social-ecological systems research provides major opportunities to advance sustainability and often involves large, interdisciplinary groups. Researchers adopt various methodologies when studying landscapes, gathering a wide array of data such as socioeconomic information from households, ecological data from specific areas, and qualitative insights from interviews. To integrate these varied methods, we propose identifying social-ecological research units as shared anchor points for data collection across teams. We outline four design principles: (i) spatial scale of social-ecological units, (ii) key social-ecological gradients in the study area, (iii) accessibility of stratification data, and (iv) flexibility in response to logistical challenges. We applied these principles to design a social-ecological study on ecosystem restoration in western Rwanda. We identified five distinct and spatially homogenous clusters, from which we sampled a total of 152 villages (~9.5% of all villages in our study area), which will be visited by different researchers within our study consortium, hence enabling to identify cross-sectional similarities and differences. Through our stratification according to these principles, we created a framework to guide interdisciplinary collaboration. This structured approach supports integration of diverse research efforts and offers insights for advancing place-based social-ecological systems research globally. Sharing our stratification data and methodology, we highlight its potential applicability to other landscapes and sustainability challenges.